ANALYSIS OF BUSINESS AND ADDED VALUE OF COFFEE BUSINESS “KOPI KEPAHIANG” IN PASAR UJUNG VILLAGE KEPAHIANG DISTRICT - Helda Indra Yenti; Reflis; Bambang Sumantri1 (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
The purpose of this research is to analyze the supply chain, the business costs of making